A A Politeness Analysis on Teachers Voices, A Pragmatics Study - Syafrianto SM (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2019)
Politeness is a visible feature in communication. A conversation is regarded as a polite conversation and an impolite one occasionally. The context is a meaningful aspect to acknowledge this meaning. It covers age, situation, place, relationship, etc. Mode of communication may also be acknowledged as a context. Along with the globalization era, mode of communication also grows and thrives to be diverse modes such as telephone and social media which enable people to communicate in face-to-face communication. One of the renowned modes is Facebook. In Facebook, as it is known that there are miscellaneous areas of people creating some groups to communicate where one may post or/ and comment on other’s wall. What the members do in point of fact is like what they do in the real conversation. As in the real society, they should also consider how to be polite in virtual communication. Thus, this paper is to discuss the politeness principles & strategies in Facebook conversation. The excerpts of the conversation are obtained from a professional group named Teachers Voices (TV). The group's members were academicians such as lecturers, teachers, graduate students and others who are interested in English language studies.